Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To convert the given point-slope form equation \( y - 5 = 3(x - 2) \) to the slope-intercept form \( y = mx + b \), we need to follow these steps:
1. Distribute the slope \(m\) on the right side:
[tex]\[ y - 5 = 3(x - 2) \][/tex]
Distribute the 3:
[tex]\[ y - 5 = 3x - 6 \][/tex]
2. Isolate \(y\) to get it in the form \( y = mx + b \):
Add 5 to both sides:
[tex]\[ y = 3x - 6 + 5 \][/tex]
3. Simplify the expression:
Combine the constant terms on the right side:
[tex]\[ y = 3x - 1 \][/tex]
So, the linear function in slope-intercept form is:
[tex]\[ f(x) = 3x - 1 \][/tex]
Therefore, the correct choice is:
[tex]\[ f(x) = 3x - 1 \][/tex]
1. Distribute the slope \(m\) on the right side:
[tex]\[ y - 5 = 3(x - 2) \][/tex]
Distribute the 3:
[tex]\[ y - 5 = 3x - 6 \][/tex]
2. Isolate \(y\) to get it in the form \( y = mx + b \):
Add 5 to both sides:
[tex]\[ y = 3x - 6 + 5 \][/tex]
3. Simplify the expression:
Combine the constant terms on the right side:
[tex]\[ y = 3x - 1 \][/tex]
So, the linear function in slope-intercept form is:
[tex]\[ f(x) = 3x - 1 \][/tex]
Therefore, the correct choice is:
[tex]\[ f(x) = 3x - 1 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.